Distinct GmASMTs are involved in regulating transcription factors and signalling cross-talk across embryo development, biotic, and abiotic stress in soybean - Kumar, Gyanendra; Arya, Monisha; Padma, Radhika; Puthusseri, Bijesh; Giridhar, Parvatam (Frontiers in Plant Science, 2022)
N‐Acetylserotonin O‐methyltransferase (ASMT) is the final enzyme involved in melatonin biosynthesis. Identifying the expression of ASMT will reveal the regulatory role in the development and stress conditions in soybean. To identify and characterize ASMT in soybean (GmASMT), we employed genome-wide analysis, gene structure, cis-acting elements, expression, co-expression network analysis, and enzyme assay. We found seven pairs of segmental and tandem duplication pairs among the 44 identified GmASMTs by genome-wide analysis. Notably, co-expression network analysis reported that distinct GmASMTs are involved in various stress response. For example, GmASMT3, GmASMT44, GmASMT17, and GmASMT7 are involved in embryo development, heat, drought, aphid, and soybean cyst nematode infections, respectively. These distinct networks of GmASMTs were associated with transcription factors (NAC, MYB, WRKY, and ERF), stress signaling, isoflavone and secondary metabolites, calcium, and calmodulin proteins involved in stress regulation. Further, GmASMTs demonstrated auxin-like activities by regulating the genes involved in auxin transporter (WAT1 and NRT1/PTR) and auxin-responsive protein during developmental and biotic stress. The current study identified the key regulatory role of GmASMTs during development and stress. Hence GmASMT could be the primary target in genetic engineering for crop improvement under changing environmental conditions.